PENGARUH NILAI FUNDAMENTAL PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN - Ni Kadek Devi Ariska Dewi,; Putu Ayu Anggya Agustina,; I Made Ryan Ananta Putra, (Juremi: Jurnal Riset Ekonomi, 2026)
This research examines whether metrics affected on Return On Assets (ROA), Net Profit Margin (NPM), Earning per Share (EPS), or Debt to Equity Ratio (DER) might influence stock prices in mining firms trading on the flatform. The research population includes 30 entities in the mining firms that listed on the Indonesia Stock Exchange in 2024. The sample are 30 mining firms was collected, with data process used multivariate linear regression techniques with the assistance of IBM SPSS 27. This research findings suggest just EPS really moves positive influence on the share value of mining companies, while ROA, NPM, or DER don't seem influence to matter much. When tested simultaneously, the four variables did not show a real impact on share values. Therefore, the most important for investors is company's liquidity. This work could help clarify what actually influences share values in mining. as well as provide practical benefits for investors and financial manager, so that they able to make an accurate investment with their analysis on their financial company.